Chronic kidney disease with malignant peripheral nerve sheath tumor of the ureter: a case report - Yin, Xinyang; Wang, Xiaodong; He, Zhenlin; Chen, Xiaolong; Wang, Qing; Jiang, Kehua (Frontiers in Oncology, 2024)
Malignant peripheral nerve sheath tumors (MPNSTs) are a complex group of malignant tumors originating from nerve cells or benign peripheral nerve sheath tumors and are commonly found in major plexus/nerve root sites such as the limbs, head, and neck. Malignant peripheral nerve sheath tumors originating in the ureter are extremely rare. Herein, we report the case of a 63-year-old patient with a malignant peripheral nerve sheath tumor of the right ureter who underwent laparoscopic radical resection of the right kidney and ureter. The patient also had stage 5 chronic kidney disease (CKD). Therefore, chemotherapy and radiotherapy were not considered. No tumor recurrence was observed during the follow-up period.